2015
DOI: 10.1017/s175173111400247x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of triaxial accelerometers to measure the lying behaviour of adult domestic horses

Abstract: Examining the characteristics of an animal's lying behaviour, such as frequency and duration of lying bouts, has become increasingly relevant for animal welfare research. Triaxial accelerometers have the advantage of being able to continuously monitor an animal's standing and lying behaviour without relying on live observations or video recordings. Multiple models of accelerometers have been validated for use in monitoring dairy cattle; however, no units have been validated for use in equines. This study teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 19 publications
3
18
0
1
Order By: Relevance
“…Use of this specific accelerometer a for behavioral data collection has been validated in dairy cows 50 but not in horses; however, the general use of triaxial accelerometers has been validated in horses. 51,52 Furthermore, placement of the accelerometer on a hind limb, as was done in the present study, reportedly yields the most accurate data. 51 In a study 53 involving calves, use of an accelerometer to examine the effect of castration revealed that castrated calves spent a significantly larger amount of time standing during the subsequent 24-hour period (or longer) than uncastrated calves, but studies [54][55][56] of the effect of lameness on cattle behavior have shown that lame cattle spend more time lying down than do nonlame cattle.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Use of this specific accelerometer a for behavioral data collection has been validated in dairy cows 50 but not in horses; however, the general use of triaxial accelerometers has been validated in horses. 51,52 Furthermore, placement of the accelerometer on a hind limb, as was done in the present study, reportedly yields the most accurate data. 51 In a study 53 involving calves, use of an accelerometer to examine the effect of castration revealed that castrated calves spent a significantly larger amount of time standing during the subsequent 24-hour period (or longer) than uncastrated calves, but studies [54][55][56] of the effect of lameness on cattle behavior have shown that lame cattle spend more time lying down than do nonlame cattle.…”
Section: Discussionsupporting
confidence: 51%
“…For horses in the present study, the number of lying bouts was approximately 10/d before shoe application. Findings of other studies 33,52,57 regarding the number and duration of lying bouts of horses greatly differ. Horses housed in groups on different types of bedding reportedly have between 2 and 3 lying bouts/d, with 32% of these horses spending a full 24-hour period without any lying bouts.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In recent years, the use of a gravitational force data logger has also been reported in research on equine standing and lying behaviors [2]. Use of this device in combination with a GPS unit would enable more detailed behavioral analyses of horses in pasture.…”
Section: Discussionmentioning
confidence: 99%